Microeconomic Drivers of Competitive Advantage: The Influence of Innovation and Digital Marketing on Rezeky Payet Business - Rezeki, Sri; Nainggolan, Elisabeth; Stefanny, Stefanny (Yayasan Riset dan Pengembangan Intelektual, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a pivotal role in driving economic growth, particularly in North Sumatra. One such MSME is Rezeky Payet Indonesia, which has recently experienced a decline in competitive advantage, as indicated by decreasing sales volume. This study investigates the influence of innovation and digital marketing as microeconomic drivers of competitive advantage in the Rezeky Payet business. The research population comprises all end consumers who have made purchases at Rezeky Payet, with an undetermined total number. Consequently, the sample size of 96 respondents was determined using the Lemeshow formula, appropriate for unknown population sizes. The results show that both innovation and digital marketing have significant partial effects on competitive advantage. Moreover, when considered simultaneously, these two variables exhibit a strong and statistically significant influence on the competitive advantage of Rezeky Payet. These findings underscore the importance of continuous innovation and effective digital marketing strategies in enhancing the competitive positioning of MSMEs.